Chemotactic response of the flavonoid daidzein and its effect on the composition of the rumen bacterial community - Galicia Jiménez, Mónica M. (2014)
Daidzein is one of common metabolites in plants and has chemotactic effect on soil bacteria that colonize the plants. There are several tests to assess bacterial chemotaxis, but none focused on rumen bacteria. Therefore, the aim of this study was to test the chemotactic response of the rumen microflora towards daidzein using a standardized bacterial chemotaxis assay. It consisted in a modifying capillary technique and employing technology for measuring in vitro gas production. Ruminal fluids and cellulose were used as controls. The response of bacteria to daidzein was greater than the response to cellulose, supporting the hypothesis that when fodder is chewed by the ruminant it releases daidzein which can attract rumen bacteria towards feed particles (chemotaxis) for attachment and subsequent degradation.